Fabricación de un aditivo anticorrosivo mediante la extracción de polifenoles de material orgánico residual (2023)
The phenomenon of corrosion is a problem that affects metallic structures due to the conditions to which they are exposed (generally the conditions implied by industrial processes are not so favorable with structures and equipment that perform storage, transportation, mixing, etc. of chemical substances). To help counteract the deterioration caused by these processes, coatings/linings or paints have been created that protect surfaces from the impact that the environment has on them.